THE USE OF BLOCKCHAIN TECHNOLOGY FOR SECURE AND TRANSPARENT MEDICAL RECORD MANAGEMENT - Abdullah Naif Abdullah Al Dawsari, Abdulrahman mulla Alanazi, Ali Saeed Mohammed Alamri, Abdullah Ali Muidh Alshehri, Sarah Atiah Mayudh Alharthi, Hend Saeed Alessa, Norah Mesfer Alqahtani, Kadijah Marzouq Alrashdi, Sarah Mabrouk H Mubarak,; Aiman Ahmed Wafi, Saadoun Obaid Namesh Al-Rashidi, Maseerah Falah Alonizy, Abdallah german ALamri-Mofarhe Yahia Mohsen Mashike, Fatimah jameel Al-Qobaii (Chelonian Research Foundation, 2022)
Electronic health records (EHRs) are crucial documents that provide comprehensive health information, but they are susceptible to security breaches, power outages, and unauthorized access. Blockchain technology offers a decentralized platform for sharing EHR data, enhancing security and decentralization. Blockchain is particularly useful for smart contracts and machine-learning algorithms. However, it faces challenges in scalability and complexity. To address these issues, integrating artificial intelligence and blockchain technology can be beneficial. AI algorithms rely on data from reliable, trustworthy, and reputable platforms for learning and decision-making. A systematic literature review (SLR) was conducted on 189 research articles on EHR management using blockchain technology, focusing on security, confidentiality, access, and sustainability. The SLR found that blockchain technology offers decentralization, security, and privacy, which are often lacking in traditional EHRs. The findings provide valuable insights for future researchers on the best choice of blockchain technology for their studies. The SLR also provides a comprehensive analysis of various healthcare approaches and their advantages and disadvantages. The integration of blockchain and AI in health records management systems allows for the exploration of potential uses. Keywords: blockchain, artificial intelligence, algorithms, literature review, electronic health records.